Evaluation of Food Knowledge and Health Awareness for Some Egyptian Hotel’s Kitchen Cooks - Ashour, Essam Zakaria; El Fattah, Mostafa Attia A.; Emam, Ahmed Mahmoud (جامعة قناة السويس - كلية السياحة والفنادق, 2013)
إن المعرفة الغذائية والوعي الصحي للطهاة العاملين في المطابخ الفندقية ذات أهمية كبيرة حيث أنه يمكن أن يؤثر على صحة وسلامة النزلاء. ولأن الطهاة هم المسئولون عن تخطيط القوائم واختيار المنتجات هذا بالإضافة إلى أنهم المسئولون عن تجهيز وطهي ما يتناوله الضيوف من وجبات غذائية متنوعة وهذه المسئولية تجعل إلمامهم الكامل والجيد بالوعي الغذائي والصحي ضروري حتى يمكنهم الوصول بقوائم الطعام والمنتجات الغذائية إلى مستوى عالي من حيث الأمان والسلامة للنزلاء بالإضافة إلى المحافظة على القيمة الغذائية لهذه الوجبات، إن هذه الدراسة تهدف إلى التعرف على مدى المعرفة الغذائية والوعي الصحي للطهاة في المطابخ الفندقية وتقييم مدى إلمامهم بمبادئ سلامة الغذاء والصحة العامة وصحة الغذاء وذلك بغرض الوصول إلى أفضل المقترحات والتوصيات للعمل على زيادة هذه المعرفة الغذائية وكذلك الوعي الصحي للطهاة في المطابخ الفندقية ، تمت الدراسة من خلال 15 فندق موزعة بمعدل 5 فنادق في ثلاثة مناطق سياحية وهي القاهرة وشرم الشيخ والغردقة وقد أظهرت النتائج أن هناك ضعف نسبي في مستوى معرفة الطباخين محل الدراسة بالوعي الغذائي والصحي وكذلك ضعف الوعي ببعض أساسيات قواعد النظافة الشخصية وسلامة وصحة الغذاء. The current study presents the findings of a quantitative study of 370 hotel cooks concerning of hotel’s kitchen cooks toward food knowledge and health awareness in Egypt. To the food knowledge and health awareness of the cooks on hotel’s kitchen great importance as it can affect the guest's health and safety. Because the cooks are responsible for planning the menus or select the food items, moreover, they are responsible for preparing and cooking a variety of meals for guests. This responsibility makes the full familiarity of health awareness and food knowledge are necessary so that they can access menus or food products to a high standard in terms of food safety and preservation of the nutritional value. This study at identifying the extent of hotel’s kitchen cooks about food knowledge and health awareness in Egypt and assess the extent of their knowledge of the principles of food safety, public health and food hygiene. In order to reach the best recommendations and suggestions for actions to increase the food knowledge and health awareness of the hotel’s kitchen cooks in Egypt. Our study included 15 hotels in three destinations Greater Cairo, Sharm El Sheikh and Hurghada (5 hotels each destination). The results for the tested cooks revealed a lack of the level of food knowledge and health awareness and some basic rules of food hygiene, safety and health.
Keywords: المعرفة الغذائية -- الوعى الصحى -- طهاة الفنادق -- الفنادة المصرية